The Influence of Organizational Culture, Work Environment, Knowledge Sharing and Motivation on Employee Performance - Dini, Ananda Putri; Deviastri, Lily (SAN Scientific, 2023)
This study aims to determine the effect of organizational culture, work environment, knowledge sharing and motivation on employee performance. The population in this study were employees of the DKI Jakarta Regional Revenue Agency. The sampling technique used was purposive sampling. The number of respondents in this study were 100 employees. the data analysis method used is multiple regression analysis, t test (partial) and F test (simultaneous). The results of the study show that: (1) Organizational Culture has a positive and significant effect on Employee Performance. (2) Work Environment has no influence on Employee Performance. (3) Knowledge Sharing has no effect on Employee Performance. (4) Motivation has a positive and significant effect on employee performance. (5) simultaneously all independent variables have a significant effect on the Performance of the DKI Jakarta Regional Revenue Agency Employees.